2009
DOI: 10.1002/ejic.200900134
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiNxO2–x Photoelectrodes with NH3 Under Controllable Middle Pressures for Dye‐Sensitized Solar Cells

Abstract: As part of our efforts to find a way to control the concentration of N‐doped TiO2, TiNxO2–x powders were prepared by a device of our own design. In this research, photoelectrodes are generated using N‐doped TiO2 materials where the concentrations are adjusted by the amount of NH3 under middle pressure, which is seldom reported. Considerable efforts have been directed to the study of the optical absorption edge that is redshifted towards the visible‐light region. Therefore, N‐doped TiO2 electrodes are character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…With bandgap modification, Khan et al [3] demonstrated a lower bandgap energy (2.32 eV) of carbon doped n-TiO 2−x C x type film synthesized by combustion of the Ti metal sheet, which absorbed light at wavelengths below 535 nm. Band-gap narrowing was also observed in nitrogen doped TiO 2 nanoparticles and the results obtained from the density functional theory (DFT) calculations shows that N-doped TiO 2 could achieve the absorption spectra broadened owing to the presence of N-impurities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 71%
“…With bandgap modification, Khan et al [3] demonstrated a lower bandgap energy (2.32 eV) of carbon doped n-TiO 2−x C x type film synthesized by combustion of the Ti metal sheet, which absorbed light at wavelengths below 535 nm. Band-gap narrowing was also observed in nitrogen doped TiO 2 nanoparticles and the results obtained from the density functional theory (DFT) calculations shows that N-doped TiO 2 could achieve the absorption spectra broadened owing to the presence of N-impurities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 71%
“…Secondly, the sintered films were put in a sealed stainless steel autoclave designed by ourselves (see Supporting information) and treated in NH3 with pressures ranging from 0 to 0.8 MPa (0, 0.2, 0.6, and 0.8 MPa) at 400 • C for 12 h. The NH3 gas with 99% purity was first purified via a device that absorbed impurities and then flowed into the reaction chamber. The heater power was not launched until the NH3 pressure reached the predetermined value [19].…”
Section: Preparationmentioning
confidence: 99%
“…[20] An enhanced photocurrent and retarded electron recombination has been observed in DSCs. [21][22][23] Therefore, we attempted to use MWCNT/ TiO 2-x N x nanocomposites as photoelectrodes to enhance electron transfer and collection, which can further improve the photovoltaic performance of DSCs.…”
Section: Introductionmentioning
confidence: 99%